2016
DOI: 10.1590/1678-4324-2016150622
|View full text |Cite|
|
Sign up to set email alerts
|

Regulating Effect Of Carnosine And /Or L- Arginine On The Expression Of Inflammatory Molecules Induced Nephropathy In The Hypoxic Rat Model

Abstract: This study aimed to explore the effective role of carnosine and /or L-arginine pro-inflammatory molecules, including tumor necrosis factor-α (TNF-α) , Creactive protein (CRP), vascular endothelial growth factor (VEGF) and heat shock protein -70 (HSP-70) as well as interleukin-6 (IL-6) in renal tissue compared to NaNO2 hypoxic rats . Also, the two agents successfully down modulated the alteration in the serum hypoxia inducible factor 1α (HIF 1α

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…Our data are similar to that of Al-Rasheed et al (2016) 32 who reported that the liberation of the former biomarkers may participate in Sod ntr.-induced kidney dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are similar to that of Al-Rasheed et al (2016) 32 who reported that the liberation of the former biomarkers may participate in Sod ntr.-induced kidney dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Pretreatment with L-Arg markedly reduced the dramatic down-regulation of HSP-60 and HSP-70 in hypoxic rat model. The increased expression of HSP-60 and HSP-70 might be related to their leakages from tissue, which can cause tissue injury due to free radical production [47,48]. Tissue injury might be caused by nitric oxide, a free radical, through the stimulation of endothelial cells and neutrophils that is generated from a higher dose of L-Arg [49].…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment with L-Arg markedly reduced the dramatic down regulation of HSP-60 and HSP-70 in hypoxic rat model. The increased expression of HSP-60 and HSP-70 might be related to their leakages of tissue in response to tissue injury [39,40]. Hence, present result may suggest that the increased level of HSP-47, HSP-60 and HSP70 in high doses of L-Arg may have the major role in tissue injury.…”
Section: Protein Analysis By Western Blotmentioning
confidence: 59%